Simulation of ecophysiological processes of growth in several annual crops: N29 - F W T. Penning de Vries (Pudoc, 1989)
This book explains physiology in a whole-crop context for those who want to apply crop growth models in a broader framework. It provides a theoretical basis, concrete models and concrete data sets for more than dozen crops. Some data about soils are also presented. The models can be used to simulate production and water use in order to survey and evaluate new sites, crops or cultivars, and husbandry and management techniques before embarking on a large program